Frecuencias de corte en el pasto Brachiaria humidicola y su efecto en la capacidad de carga en Zungarococha-2019 - Saldaña Rojas, Maria del Carmen (2021)
The Work was developed in the Shop of Teaching and Investigation Garden Agrostologico, located in the Km. 5,800 of the highway Iquitos - Zungarococha, Saint John the Baptist District, County of Maynas, Department of Loreto, with the objective of evaluating the court frequency to the (4ta, 5ta, 6ta and 7ma week) of the Coix lacrima-jobi and their effect in their agronomic characteristics in the I found Zungarococha, the population was conformed by the plants of the grass Coix lacrima-jobi for bed of 10m2 c/u one had 40 plants that which makes a total of 480 plants (12 beds), the Design of Complete Blocks was used at random, with four (4) treatments and three (3) repetitions, with the obtained results can conclude: That the T3 (evaluation to the 7ma week) it occupies the first place the variable height (2.16 cm), green matter (7.70 kg/m2) and dry matter (1.86 kg/m2), in second place the T2 is located (evaluation to the 6ta week) with averages of height (2.01 cm), green matter (4.73 kg/m2) and dry matter (1.14 kg/m2); this is convenient to know it for that the nutritional quality of a forage (CHO) it is then in its good point to the 6ta week it begins to fall affecting the production and productivity of the animals. With respect to the hypothesis outlined work presently this it is accepted, since the evaluations carried out according to the times of evaluation (4ta, 5ta, 6ta and 7ma week) if they are affected significantly in the plant height, green matter and dry matter of the grass in study.